Aggressive periodontitis in a 16-year-old Ghanaian adolescent, the original source of Actinobacillus actinomycetemcomitans strain HK1651 – a 10-year follow up - D. HAUBEK, A. HAVEMOSE-POULSEN, & J. WESTERGAARD (Paediatric Dentistry, 2006)
In 1994, Brogan and co-workers showed that Actinobacillus actinomycetemcomitans strains characterized by a 530-bp deletion in the promoter region of the leukotoxin gene operon, called JP2 strains after the first isolate of this type [1], had an increased production of leukotoxin compared to A. actinomycetemcomitans strains without the 530-bp deletion (non-JP2 types) [2].